Ralph Compton : [large type] the sagebrush trail - Compton, Ralph; Randisi, Robert J. (Compton, Ralph. Trail drive series, 2022)
"Capturing and breaking wild horses is a tough way to make a living. But Montana ranch owner, Ethan Miller's problems are just getting started. First the buyer he has for his herd falls through. The only other outlet he can find is the US cavalry. That means driving 200 horses all the way from Bozeman, Montana to Fort Davis, Texas. No sooner has he made the dangerous trek than one more obstacle presents itself. The fort's commander needs Ethan's help. A shipment of rifles and ammunition is missing. The commander is willing to lead his men after them, but he has no scout. Since Ethan has plenty of years of scouting experience, he's going to have to lead one more mission if he hopes to get paid."--